Control of standing balance while using constructions stilts: comparison of expert and novice users. Issue 2 (1st February 2016) - Noble, Jeremy W.; Singer, Jonathan C.; Prentice, Stephen D.
Abstract : This study examined the control of standing balance while wearing construction stilts. Motion capture data were collected from nine expert stilt users and nine novices. Three standing conditions were analysed: ground, 60 cm stilts and an elevated platform. Each task was also performed with the head extended as a vestibular perturbation. Both expert and novice groups exhibited lower displacement of the whole body centre of mass and centre of pressure on construction stilts. Differences between the groups were only noted in the elevated condition with no stilts, where the expert group had lower levels of medial–lateral displacement of the centre of pressure. The postural manipulation revealed that the expert group had superior balance to the novice group. Conditions where stilts were worn showed lower levels of correspondence to the inverted pendulum model. Under normal conditions, both expert and novice groups were able to control their balance while wearing construction stilts. Abstract : Practitioner Summary: This work investigated the effects of experience on the control of balance while using construction stilts. Under normal conditions, expert and novice stilt users were able to control their balance while wearing construction stilts. Differences between the expert and novice users were revealed when the balance task was made more difficult, with the experts showing superior balance in these situations.